Butler and Ecumenism as a Theological Category in the Implementation of Vatican II: The Theological Significance of Abbot Christopher Butler's Conciliar Letters and Diaries. Issue 1 (May 2016) - Morgan, Stephen
Abbot Christopher Butler of Downside Abbey attended Vatican II as Abbot President of the English Benedictine Congregation. He was, arguably, one of the most distinguished and influential English-speaking theologian at the Council but his theological formation had not been within the normal Roman Catholic seminary or Pontifical University system. Both as an Anglican and then, after his conversion to Roman Catholicism, as a Benedictine, his education gave him a very distinct theological approach. This approach together with his close personal contacts in his former communion ensured that ecumenical matters were a major concern of his participation at the Council. For Butler, Christian Unity was more than an ecclesiological imperative but became a theological category to which the entire conciliar project was to be formed. He will argue that, through his 1966 Sarum lectures, published as 'The Theology of Vatican II', and his long-lasting influence as a member of the Bishops' Conference of England and Wales, Butler was the single most important home-grown theological influence refashioning and reorienting English and Welsh Roman Catholicism in an ecumenical direction, and that this has had a determining effect on the readiness of it for the New Evangelisation.